Simulasi Kinerja Thermodinamika AC Split Menggunakan Refrigeran R32, R1234yf, dan R290 - Lamawuran, Marianus Adventus; Gurnawati, Gurnawati; Dwinanto, Matheus Magnus (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2024)
Split AC is the process of regulating temperature, humidity, cleanliness, and air distribution in a room so as to achieve thermal comfort conditions for the occupants in it. The purpose of this research is to simulate the thermodynamics of a Split AC using environmentally friendly refrigerants R32, R1234YF, and R290 using Genetron Propertis software version 1.4.1. The method used in this study is a standard air conditioning performance simulation using R32, R1234YF, and R290 refrigerants with Genetron Propertis software version 1.4.1. The simulation results of the basic cycle refrigeration system performance with the working fluid R32 for the condensation temperature are maintained constant, because the temperature of the refrigerant gas through the condenser must be higher than the ambient temperature, condensation occurs in the condenser, so that the refrigerant changes form to liquid. From the simulation of the split AC thermodynamic performance, an increase in the evaporation temperature will have a significant impact on increasing the consumption of pumping power, increasing the mass ratio, and COP in the system.